Switched Injection Locked Oscillator: A Novel Versatile Concept for Wireless Transponder and Localization Systems - Vossiek, Martin; Gulden, Peter (IEEE Transactions on Microwave Theory and Techniques, 2008)
In this paper, the novel principle of the switched injection-locked oscillator is introduced. It is shown that the concept is ideally suited for transponder and secondary radar systems with outstanding performance. A switched injection-locked oscillator transponder can produce an approximately phase coherent high-power response to an interrogating signal and, consequently, allows for long-range transponder systems and precise distance measurement between the reader and transponder. The simple and elegant round-trip time-of-flight measurement concept introduced in this paper enables innovative localization and navigation systems. Furthermore, it can be applied in numerous areas such as sensor networks, RF identification and localization, ubiquitous computing, location sensitive billing, context dependent information services, or tracking and guiding. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.LEH.switch
Keywords: Backscatter transponder; Oscillators; Radar; Radio navigation; Radio position measurement; RF identification (RFID); Secondary radar; Transponders